GlycoBIST: A System for Automatic Glycan Profiling of a Target Protein Using Milli‐Bead Array in a Tip. (19th February 2020) - Shimazaki, Hiroko; Ono, Ayaka; Tsuruga, Masako; Ueki, Aya; Koseki‐Kuno, Shiori; Toyoda, Takako; Saito, Kozue; Sawakami, Kazumi; Kariya, Minoru; Segawa, Osamu; Nakamura, Kazuhiro; Koizuka, Michinori; et al.
Abstract: Lectin is a biomolecule that recognizes a specific part of glycans and, thus, has been used widely as a probe for glycoprotein analysis. Owing to the wide repertoire in nature combined with the recent two decades of advances in microarray technology, the multiplexed use of lectins has been widely used for glycan profiling of endogenous proteins. Because protein glycosylation is recognized as being biologically important and is expected to be a reliable disease marker, lectin microarray analysis with highly sensitive detection has been used to discover disease‐relevant glycosylation alterations. However, the conventional system is limited to research purposes; thus, its implementation in clinical settings is warranted. Here, we provide an automatic glycan profiling method using GlycoBIST. A unique array format is used for 10‐plexed lectin–glycoprotein interaction analysis on 1‐mm‐sized beads, which are arranged vertically in a capillary‐shaped plastic tip. Using a one‐boxed autopipetting machine, the whole process (including interaction, washing, and detection) is performed automatically and serially, resulting in reproducible measurements. In this article, a typical method for glycan profiling of a purified glycoprotein and the fabrication of GlycoBIST tips is explained. © 2020 by John Wiley & Sons, Inc. Basic Protocol 1 : Fabrication of a GlycoBIST tip Basic Protocol 2 : Automatic profiling of a target glycoprotein using GlycoBIST